ID30B – a versatile beamline for macromolecular crystallography experiments at the ESRF. (27th June 2018) - McCarthy, Andrew A.; Barrett, Ray; Beteva, Antonia; Caserotto, Hugo; Dobias, Fabien; Felisaz, Franck; Giraud, Thierry; Guijarro, Matias; Janocha, Robert; Khadrouche, Akim; Lentini, Mario; Leonard, Gordon A.; et al.
Abstract : ID30B, a versatile macromolecular crystallography beamline at the ESRF, is presented. Abstract : ID30B is an undulator‐based high‐intensity, energy‐tuneable (6.0–20 keV) and variable‐focus (20–200 µm in diameter) macromolecular crystallography (MX) beamline at the ESRF. It was the last of the ESRF Structural Biology Group's beamlines to be constructed and commissioned as part of the ESRF's Phase I Upgrade Program and has been in user operation since June 2015. Both a modified microdiffractometer (MD2S) incorporating an in situ plate screening capability and a new flexible sample changer (the FlexHCD) were specifically developed for ID30B. Here, the authors provide the current beamline characteristics and detail how different types of MX experiments can be performed on ID30B (http://www.esrf.eu/id30b ).